A Cluster of Three Cases of Hantavirus Pulmonary Syndrome among Canadian Military Personnel - Leighanne O. Parkes; Trong Tien Nguyen; Jean Longtin; Marie-Claude Beaudoin; Julie Bestman-Smith; Donald C. Vinh; Guy Boivin; Vivian G. Loo (Canadian Journal of Infectious Diseases and Medical Microbiology)
Hantavirus pulmonary syndrome (HPS) is a rare illness in eastern Canada. We present three cases of HPS among military personnel in Quebec. The three cases shared a common exposure to mouse excreta while engaged in military training in Alberta, a western province of Canada.